Reconstruction of Utilization Arrangements for the State Assets in the Form of Land to Increase Non-Tax State Revenue - Sitindaon, Iwan Victor Leonardo; Febrian, Febrian; Ridwan, Ridwan; Rumesten, Iza (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Article 33 of the 1945 Constitution of Republic Indonesia mandates the urgency of optimizing the management of state assets, whether in the management of controlled state assets, owned state assets, or separated state assets for improving the maximum benefit of the prosperity of the folk to create a prosperous state (welfare state). One form of owned state wealth is referred to as State Property/Assets (hereinafter abbreviated as BMN).Purposes of the Research: The author is interested in writing this article because there are still many BMN that are indicated to be vacant, neglected, and not used optimally, whereas this optimization of BMN is able to make a positive contribution to PNBP. This thing must be supported by strict and definite regulations about the management and utilization of BMN.Methods of the Research: The research methodology used in this study is legal research with a normative juridical study using a statutory approach and this theoretical concept uses several legal materials to support the data and theory.Results of the Research: The utilization of BMN in the form of land has not been optimal due to: the approval of the utilization of BMN by the Property Manager is not immediately followed up with a utilization agreement by a third party on the grounds that the utilization rate is still high; there is no regulation that regulates the objections of the fair value of BMN that will be utilized; the application of sanctions is not firm and there are articles on the management and utilization of BMN which are vague (vage normen).